Do personalisation and emotions affect the use of cancer-related websites?. Issue 1 (13th February 2017) - Hadžidedić Baždarević, Sunčica; Cristea, Alexandra Ioana
Abstract : Purpose: The purpose of this paper is to explore the type of personalisation services satisfying the needs of cancer websites' target users, and the influence of their emotional states on website usage intentions. Design/methodology/approach: Three data collection methods were employed. Survey questionnaires were distributed to online health users. Interviews with representatives of the cancer-affected population further explored emotions as stimuli for online cancer-related activities. Finally, availability of personalisation features was evaluated on existing health websites in Bosnia and Herzegovina and the UK. Findings: A clear preference emerged for personalisation on cancer-related websites. There are specific personalisation features the cancer-affected population desires. Interestingly, certain emotions were found to stimulate visits to health websites. Research limitations/implications: Fighting cancer implies constant support, including from cancer-related websites. It is thus vital to understand the required personalisation, stemming from target users' actual needs, including the neglected user characteristics, as are emotions for cancer-affected people. This supports emotion-based personalisation. Originality/value: The paper focusses on the cancer-affected population, and developing a comprehensive understanding of their personalisation needs in online health services. It further shows which emotions influence intentions to use cancer websites. The three concepts combined have not yet been studied, to the best of the authors' knowledge.